2013
DOI: 10.1007/s11356-013-1777-8
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated alkylated substances in vegetables collected in four European countries; occurrence and human exposure estimations

Abstract: The human diet is recognised as one possible major exposure route to the overall perfluorinated alkylated substances (PFAS) burden of the human population, resulting directly from contamination of dietary food items, as well as migration of PFAS from food packaging or cookware. Most European countries carry out national monitoring programs (food basket studies) to monitor contamination with pollutants. Usually, for PFASs, non-coordinated approaches are used in Europe, since food basket studies are mainly carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 47 publications
1
53
2
Order By: Relevance
“…The selection of food items was based on several equally important criteria described by Herzke et al (2013): (1) relevance of the intakes for the selected European area, (2) lack of data on PFAA concentrations in food, and (3) practicability of the sampling strategy according to human, instrumental and budgetary resources available within the PERFOOD project. For the PERFOOD project, food items representing 14 categories suggested by EFSA (EFSA, 2011a) were sampled.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of food items was based on several equally important criteria described by Herzke et al (2013): (1) relevance of the intakes for the selected European area, (2) lack of data on PFAA concentrations in food, and (3) practicability of the sampling strategy according to human, instrumental and budgetary resources available within the PERFOOD project. For the PERFOOD project, food items representing 14 categories suggested by EFSA (EFSA, 2011a) were sampled.…”
Section: Samplingmentioning
confidence: 99%
“…The PFAA concentrations and the dietary intake estimation for such food items are presented in this work. Studies by Herzke et al (2013) and Hlouskova et al (2013) report the results for vegetables and food items of animal origin, respectively, and, together with a detailed exposure estimation study by Klenow et al (2013) describe the overall aims, sampling procedures and handlings within the PERFOOD project.…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing number of studies have emphasized the importance of dietary intake as an exposure pathway Fromme et al, 2009;Harada and Koizumi, 2009;Vestergren et al, 2008). Seafood and freshwater fish have been identified as important contributors to dietary exposure to PFOS and long-chain PFCAs Berger et al, 2009;Fromme et al, 2009;Haug et al, 2010;Rylander et al, 2010), whereas a varied picture has been seen for other PFASs (Herzke et al, 2013;Vestergren et al, 2012). In addition, several biological factors play a role in the burden of PFASs in the body, including age, gender, reproductive factors, and compound specific toxicokinetics Denys et al, 2014;Harada and Koizumi, 2009;Haug et al, 2010;Lorber et al, 2015;Miralles-Marco and Harrad, 2015;Nost et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The long environmental residence may also result in an increased cumulative transfer of PFOA from water and soil into plants (Blaine et al, 2014a;Herzke et al, 2013;Lechner and Knapp, 2011;Sepulvado et al, 2011;Yoo et al, 2011). A number of studies have shown that plants can take up PFOA from contaminated irrigation water (Blaine et al, 2014b;Felizeter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%